Robotic approach in case of thymoma involving the left anonymous vein: a case report - Solinas, Michela (AME Case Rep, 2017)
The robotic system has several technical advantages over the manual video thoracoscopic approach. It offers a high definition three-dimensional view and robotic arms are more comfortable to use, because they allow more precise, flexible, and intuitive movements. This case report describes a locally advanced thymoma in a 75-year-old male patient, excised through a robotic-assisted thymectomy with atypical resection of the infiltrated left upper lobe, the preservation of the left phrenic nerve and partial resection of the left anonymous vein involved, without necessity of reconstruction. Clinical staging was thymoma T3 B1–2, while the postoperative histological classification and radiation was thymoma T3, B3, Masaoka-Koga stage IIB. The postoperative course was uneventful and the patient was discharged in second postoperative day. This case remarks that robotic devices are of great help in the intraoperative recognition and precise management of infiltrated structure, like important vessels and nerves, avoiding conversion to an open approach, which until now was the main surgical indication in these situations.